Privacy and Trade Secret Law Applied to Drones: An Economic Analysis - Hazel, Robert A. (Science and Technology Law Review, 2018)
The growing number of commercial and consumer drones, combined with their ability to fly quietly at low altitudes with cameras and other monitoring equipment, raises concerns about privacy and property rights. This Article focuses on two primary questions. First, how will the balancing of privacy concerns and the interests of drone operators influence the emergence of new rules governing minimum drone operating altitudes above private property? And, second, once those new rules are set, how will the large volume of drone operations affect existing laws? An economic analysis of intrusion upon seclusion and trade secret law helps answer these questions. Permitting drones to fly above private property without the property owner’s consent provides efficiency gains by enabling drones to fly more directly to their destinations. And, as with planes flying at high altitude, most landowners are unlikely to notice overhead drones operating at an altitude of at least 200 feet. Thus, the benefits of reducing vertical property rights to create a 200- to 400-foot high public highway for drones, as the Federal Aviation Administration is considering, are likely to far exceed the costs. However, at sufficiently low altitudes, drones impose significant privacy costs because of their surveillance capabilities and unsettling proximity. Permitting drones to fly at less than 200 feet would provide only minimal additional economic benefits to the drone industry while significantly increasing potential privacy costs for individuals. Accordingly, because the privacy costs imposed by drone operations below 200 feet would exceed efficiency benefits gained, drone operations below this height should be considered a trespass and property owners should be permitted to exclude them. Operations above 200 feet present a different set of challenges because drones operating at that height are, or soon will be, capable of capturing detailed images of property below. For those operations, individuals will still need to rely on intrusion law to protect their privacy, and firms will still need to rely on trade secret law to protect their commercial secrets. The original economic rationales for both laws continue to apply in the drone era. Intrusion law recognizes that protecting the seclusion of individuals is economically beneficial. Trade secret law recognizes that there are economic benefits to affording trade secret protection to firms that take reasonable precautions to protect their commercial secrets. Although the rise of drones need not change intrusion and trade secret legal principles, the large number of drones means that new simple rules should be issued to establish a presumption of intrusion upon seclusion. The large number of drones also means that firms may need to take additional precautions to benefit from trade secret protection both as a legal matter and for practical reasons. Another recommendation is for higher penalties and more frequent use of punitive damages.